THE URGENCY OF LAND ADMINISTRATION ACCURACY BY THE NATIONAL LAND AGENCY TO MINIMIZE LAND DISPUTES - Noval Abi Putra; Mahipal; Mustaqim (Awang Long Law Review, 2026)
As the agency authorized to issue State Administrative Decisions (TUN) in the land sector, the National Land Agency (BPN) has a legal obligation to ensure that all administrative processes are carried out meticulously, accurately, and in accordance with the General Principles of Good Governance (AUPB). This research aims to analyze the application of the principle of prudence by BPN officials in the process of issuing land certificates and to examine the form of state responsibility when there is a violation of this principle. This research employs a normative legal research method with a legislative and conceptual approach, supplemented by an analysis of several relevant State Administrative Court (PTUN) decisions. The research findings indicate that the negligence of BPN officials in verifying legal data and conducting physical inspections of land can be categorized as a violation of the principle of diligence, which has implications for the cancelation of land administration decisions and the emergence of state liability. Therefore, the application of the principles of prudence and transparency in every stage of land administration needs to be strengthened so that public trust in the agrarian legal system and the protection of land rights in Indonesia remains protected.